Pengaruh Pendekatan Belajar Terhadap Hasil Belajar Pengantar Akuntansi 1 - Suci Wulandari; Sany Dwita; Halmawati Halmawati (Universitas Negeri Padang, 2019)
This study aims to determine empirically the effect of learning on learning outcomes approach Accounting I. Introduction The research is a quantitative research. The population in this study were students majoring in Accounting, Economics Faculty S1 at Padang State University from 2017 to 2018. The sampling technique used in this research is purposive sampling as many as 189 people who of force in 2017, 2015 and 2014. The data collection method used survey method in the form of a questionnaire given personally. The data processing was performed using SPSS. The results of this study indicate that in-depth approach, strategic approach and surface approach simultaneously significant effect on learning outcomes. Contribution approach used in the study affect learning outcomes is quite large, namely by 50% and approaches to learning most significant influence is the strategic approach, this is evidenced from t to the variable strategic approach by 2,599> t table 0,010 1,652 significance <0.05 and then.